Dwight Lyman Moody papers - Moody, Dwight Lyman, 1837-1899.; Whittle, D. W. (Daniel Webster), 1840-1901.
General and family correspondence, sermon notes, scrapbooks, and miscellaneous printed matter relating to Moody's work as an evangelist; the Northfield Seminary for Young Ladies, East Northfield, Mass.; the Mount Hermon School, Mount Hermon, Mass.; and family and financial affairs. Includes a Civil War diary (1864) kept by D.W. Whittle while serving under General William T. Sherman in Georgia. Correspondents include John D. Cutter, Cyrus Holton, William F. Lee, and Henry William Rankin.
Evangelist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Cutter, John D. -- Correspondence; Holton, Cyrus, -- 1813- -- Correspondence; Lee, William F., -- active 1882-1887 -- Correspondence; Rankin, Henry William, -- 1852-1937 -- Correspondence; Sherman, William T. -- 1820-1891.; Moody family; Mount Hermon School; Northfield Seminary for Young Ladies; Education -- Massachusetts; Evangelistic work -- United States; Schools -- Massachusetts; Georgia -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; Evangelists